The effect of thoracic kyphosis and sagittal plane alignment on vertebral compressive loading - Bruno, Alexander G; Anderson, Dennis E; D'Agostino, John; Bouxsein, Mary L (Journal of bone and mineral research, 2012)
To better understand the biomechanical mechanisms underlying the association between hyperkyphosis of the thoracic spine and risk of vertebral fracture and other degenerative spinal pathology, we used a previously validated musculoskeletal model of the spine to determine how thoracic kyphosis angle and spinal posture affect vertebral compressive loading. We simulated an age‐related increase in thoracic kyphosis (T1–T12 Cobb angle 50–75 degrees) during two different activities (relaxed standing and standing with 5‐kg weights in the hands) and three different posture conditions: (1) an increase in thoracic kyphosis with no postural adjustment (uncompensated posture); (2) an increase in thoracic kyphosis with a concomitant increase in pelvic tilt that maintains a stable center of mass and horizontal eye gaze (compensated posture); and (3) an increase in thoracic kyphosis with a concomitant increase in lumbar lordosis that also maintains a stable center of mass and horizontal eye gaze (congruent posture). For all posture conditions, compressive loading increased with increasing thoracic kyphosis, with loading increasing more in the thoracolumbar and lumbar regions than in the mid‐thoracic region. Loading increased the most for the uncompensated posture, followed by the compensated posture, with the congruent posture almost completely mitigating any increases in loading with increased thoracic kyphosis. These findings indicate that both thoracic kyphosis and spinal posture influence vertebral loading during daily activities, implying that thoracic kyphosis measurements alone are not sufficient to characterize the impact of spinal curvature on vertebral loading. © 2012 American Society for Bone and Mineral Research.